2017
DOI: 10.1002/2017gl073821
|View full text |Cite
|
Sign up to set email alerts
|

Extensive Amazonian‐aged fluvial channels on Mars: Evaluating the role of Lyot crater in their formation

Abstract: Widespread Amazonian‐aged fluvial channels have been mapped proximal to Lyot crater, a ~225 km diameter impact basin in the northern lowlands of Mars. Comparable in area to some Noachian/Hesperian fluvial systems, their morphology differs, being dominated by broad, shallow braided channels. Using new developments in the study of cratering, water inventory, and climate history, we assess eight different models for their origin. Dewatering of excavated ice‐rich Lyot ejecta and contact melting from hot Lyot eject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…Furthermore, the largest Amazonian impact (~225 km diameter Lyot crater) does not appear to have produced global or regional rainfall (Weiss et al. ).…”
Section: Outlining and Documenting The Icase Modelmentioning
confidence: 99%
“…Furthermore, the largest Amazonian impact (~225 km diameter Lyot crater) does not appear to have produced global or regional rainfall (Weiss et al. ).…”
Section: Outlining and Documenting The Icase Modelmentioning
confidence: 99%
“…In search for associated mineralogical traces of fluvial activities, we find no hydrous mineral detections associated to the fluvial channels north of Lyot extending from its ejecta blanket, which are a sign of postimpact, and likely impact‐induced, fluvial activity (Harrison et al, ; Weiss et al, ), in contrast to the diverse hydrous mineralogy found within Lyot crater and other smaller craters. Although dust cover may mask some potential mineral detections, we find it unlikely that dust cover is the sole reason for the lack of detection of hydrous minerals, in particular with various exposures of smaller complex craters and scarps in this region and the relatively light dust cover compared to Deuteronilus Mensae (Ruff & Christensen, ), where hydrous minerals have been identified.…”
Section: Discussionmentioning
confidence: 67%
“…Channelized scablands are found to the north of Lyot outside the ejecta blanket (Harrison et al, ) with only a few small, morphologically distinct channels recently identified on the ejecta (Weiss et al, ). Thirty‐two CRISM‐targeted images were examined (see Table ) north of Lyot crater covering the region where fluvial channels have been previously identified, and we did not identify any hydrous minerals.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cassanelli et al () reported the late Noachian Icy Highlands, which describes about the distribution of ice at the surface. In such scenario, possible channel origins form the contact melting from ejecta (Weiss et al, ) or thermal anomaly of impacts and their ejecta over ice‐bearing terrains forms channels (Mangold, ). However, in Reuyl crater, no channels are observed over the ejecta blanket and its immediate surrounding vicinity.…”
Section: Discussionmentioning
confidence: 99%